Prognostic Role of NLR, PLR and MHR in Patients With Idiopathic Pulmonary Fibrosis - Chen, Yiran; Cai, Jingya; Zhang, Mengmeng; Yan, Xin (Frontiers in Immunology, 2022)
Background: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive interstitial lung disease with low survival time. Since the pathophysiological progression of IPF is closely associated with immunological and inflammatory responses, immune biomarkers, including neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and monocyte-high density lipoprotein ratio (MHR), have the potential to predict overall survival in IPF patients. Methods: A total of 278 patients with IPF were finally enrolled. The demographic and clinical characteristics of the patients at baseline were recorded. Multivariable Cox regression analysis was used to evaluate the association between the three biomarkers and overall survival in both the total cohort and acute exacerbation subgroup. Results: The median follow-up was 5.84 months. After adjusting for confounders, we found that only elevated NLR was associated with worse overall survival (OR = 1.019, 95% CI 1.001-1.037, P =0.041) by using multivariable Cox regression analysis. In 116 acute exacerbation IPF patients, the results of the Cox multiple regression model also indicated that the NLR was a significant prognostic factor (OR= 1.022, 95% CI 1.001-1.044, P =0.036). The NLR before death was also significantly higher than that at admission in nonsurvival acute exacerbation IPF patients (P=0.014). No significant differences were found in PLR (P=0.739) or MHR changes (P=0.478). Conclusions: Our results indicated that elevated NLR expression is associated with shorter overall survival in IPF patients, which is independent of other prognostic factors. The NLR may be regarded as a reliable prognostic biomarker for IPF patients.